Análisis del consumo energético del sistema de iluminación y su calidad en la planta procesadora de leche Parmalat S.A., mediante medición y simulación. - Arequipa Tandalla, Mario Dario (2017)
At the “Parmalat” Milk Processing Plant S.A., the lighting system energy consumption and the lighting level quality were evaluated through the lighting study, power and installed load in order to generate a proposal to improve the mentioned indicators. On the economic technical study was based the research proposal, in which taking advantage of the computer tools was carried out a lighting analysis where the areas that did not comply with the norms and the visual comfort were analyzed. By the calculation and simulation were redesigned areas that represented the biggest problem, where the simulation of light scenes was performed in the DIALux and Excel software, thus verifying the dark spots elimination in areas that must be fully illuminated, for the compliance verification with a good illumination level, the results were compared with the help of INEN 1-154 (Natural Building Lighting for Factories and Workshops, Requirements) and NEC 11 (Ecuadorian Construction Standard). The current energy consumption by lighting is considerable due to the existing luminaire type, where different types of lamps are located in the same area, so after analysis it is proposed to relocate according to type and power in areas of medium and low consumption, according to this analysis it is proposed to use LED luminaire for the design in areas that present illumination problems and high energy consumption, generating energy savings of 23% compared to the current lighting system.